Step-by-step explanation:
by using y=uv derivative formula and stationary mean y' = 0
y' = 3(x–2)⁴ + 3(3x–1)(x–2)³ = 0
cancel 3 and factorize
(x–2+3x–1)(x–2)³ = 0
x = ¾ or x = 2
we got point
and (2,0)
Answer:
x + Y = 39 or x = 39-y
20x + 50y = 1.40
20 (39 - y) + 50y = 11.40
7.80 - 20y + 50y = 11.40
30y = 11.40 - 7.80
30y = 3.60
y = 3.60/30
y = 12 50p coins were collected.
x = 39 - 12 = 27 20p coins were collected.
Proof:
20*27 + 50*12 = 11.40
5.40 + 6 = 11.40
11.40 = 11.40
I hope it helps.
Answer: g = 42
Step-by-step explanation:
g/3 + 11 = 25
First, subtract 11 to both sides
g/3 = 14
Then, multiply 3 to both sides to get rid of the fraction
g=42
Answer:
1.938 x 10^3
Step-by-step explanation:
1938 move decimal 3 times to left and times by 10 to 3rd
<em>Note: I am assuming the first equation is:</em>
<em>x+y = 3</em>
Answer:
The solution to the system of equations is:
(x, y) = (-2, 36)
Therefore, the x-coordinate of the solution of the system
x = -2
Step-by-step explanation:
Given the system of equations
![\begin{bmatrix}x+y=34\\ x-y=-38\end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7Dx%2By%3D34%5C%5C%20x-y%3D-38%5Cend%7Bbmatrix%7D)
subtracting the equations
![x-y=-38](https://tex.z-dn.net/?f=x-y%3D-38)
![-](https://tex.z-dn.net/?f=-)
![\underline{x+y=34}](https://tex.z-dn.net/?f=%5Cunderline%7Bx%2By%3D34%7D)
![-2y=-72](https://tex.z-dn.net/?f=-2y%3D-72)
solve -2y for y
![-2y=-72](https://tex.z-dn.net/?f=-2y%3D-72)
Divide both sides by -2
![\frac{-2y}{-2}=\frac{-72}{-2}](https://tex.z-dn.net/?f=%5Cfrac%7B-2y%7D%7B-2%7D%3D%5Cfrac%7B-72%7D%7B-2%7D)
![y=36](https://tex.z-dn.net/?f=y%3D36)
For x+y=34 plug in y = 36
![x+36=34](https://tex.z-dn.net/?f=x%2B36%3D34)
Subtract 36 from both sides
![x+36-36=34-36](https://tex.z-dn.net/?f=x%2B36-36%3D34-36)
Simplify
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
Thus, the solution to the system of equations is:
(x, y) = (-2, 36)
Therefore, the x-coordinate of the solution of the system
x = -2